2023
DOI: 10.3389/fpsyg.2022.1041391
|View full text |Cite
|
Sign up to set email alerts
|

Is the myth of left-wing authoritarianism itself a myth?

Abstract: Is left-wing authoritarianism (LWA) closer to a myth or a reality? Twelve studies test the empirical existence and theoretical relevance of LWA. Study 1 reveals that both conservative and liberal Americans identify a large number of left-wing authoritarians in their lives. In Study 2, participants explicitly rate items from a recently-developed LWA measure as valid measurements of authoritarianism. Studies 3–11 show that persons who score high on this same LWA scale possess the traits associated with models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 112 publications
(213 reference statements)
0
5
0
Order By: Relevance
“…This implies that people high in RWA may be supportive of governments that enable strict measures during crises, such as border closures and lockdowns, irrespective of whether such responses are championed by traditional right-wing elites. Given that prior research shows that left-wing authoritarianism (LWA) is also positively associated with a desire for COVID-19 restrictions (Conway et al, 2023), our results highlight that RWA and LWA may be shaped by similar motivations, such as group security and conformity, despite their apparent conceptual distinctions (Altemeyer, 1996;Costello et al, 2022). Indeed, a recent study also situated in New Zealand's unique context showed that both left-and right-wing individuals supported items reflecting the authoritarian submission dimension of RWA during the country's nationwide lockdown in 2020 (Winters et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that people high in RWA may be supportive of governments that enable strict measures during crises, such as border closures and lockdowns, irrespective of whether such responses are championed by traditional right-wing elites. Given that prior research shows that left-wing authoritarianism (LWA) is also positively associated with a desire for COVID-19 restrictions (Conway et al, 2023), our results highlight that RWA and LWA may be shaped by similar motivations, such as group security and conformity, despite their apparent conceptual distinctions (Altemeyer, 1996;Costello et al, 2022). Indeed, a recent study also situated in New Zealand's unique context showed that both left-and right-wing individuals supported items reflecting the authoritarian submission dimension of RWA during the country's nationwide lockdown in 2020 (Winters et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Conflict over pandemic management has been attributed to ideological divides between liberals who endorse protective measures (such as lockdowns) and conservatives who oppose them (Conway et al., 2023; Gollwitzer et al., 2020; Van Bavel et al., 2020). Such findings do, however, contradict previous work showing that conservatives are more threat sensitive (Hibbing et al., 2014), including to diseases (Inbar et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, "regular" conservatives and liberals exhibited saliently lower figures. It is necessary to emphasize that in CEE, authoritarianism has also been detected within the left-leaning spectrum or on both poles of the left-right scale (De Regt et al, 2011;Aspelund et al, 2013;Conway et al, 2022). Hatemi and McDermott (2012) felicitously foreground that the overall complexity of this type of research is being amplified by the "chicken-and-egg problem."…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that there is increasing evidence of left-wing authoritarianism (LWA) and that LWA and RWA can share similar features, such as dogmatism, cognitive rigidity, and threat sensitivity (Conway et al, 2018;Costello et al, 2022). A recent study showed that ecological stress has similar effects on both LWA and RWA (Conway et al, 2023). Therefore, it would be intriguing for future research to test whether cultural tightness could result in the body preference of leaders via both RWA and LWA.…”
Section: Limitations and Future Avenuesmentioning
confidence: 99%